Hypsometric Analysis and Tectonic Activity Evaluation in the Semangko Fault Zone: A Literature Review - Gultaf, Hikhmadhan (Manunggal Halim Jaya, 2023)
This comprehensive review synthesizes and analyzes current literature on hypsometric analysis and its application in evaluating tectonic activity within the Semangko Fault Zone, a critical segment of the Sumatran Fault system. The study examines how hypsometric curves (HC) and hypsometric integrals (HI) serve as quantitative indicators of landscape evolution and tectonic deformation. By critically analyzing existing research, this review highlights the strong correlation between high HI values and areas of active tectonic uplift within the fault zone. The paper also explores the integration of hypsometric analysis with other geomorphic indices and its potential in seismic hazard assessment. Our findings underscore the significance of hypsometric analysis as a valuable tool in understanding the complex tectonic processes shaping the Semangko Fault Zone and its implications for regional seismic risk evaluation and land-use planning.